2019
DOI: 10.3389/fpls.2019.01486
|View full text |Cite
|
Sign up to set email alerts
|

G65V Substitution in Actin Disturbs Polymerization Leading to Inhibited Cell Elongation in Cotton

Abstract: The importance of the actin cytoskeleton for proper cell development has been well established in a variety of organisms. Actin protein sequences are highly conserved, and each amino acid residue may be essential for its function. In this study, we report the isolation and characterization of GhLi 1 from an upland cotton mutant Ligon lintless-1 (Li1), which harbors the G65V substitution in its encoded actin protein. Li1 mutants exhibit pleiotropic malformed phenotypes, including dwarf plants, distorted organs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…Actin is one of the most conserved proteins in eukaryotes. Structural predictions suggested that the G65V substitution would affect the polymerization capability of GhACT17DM, as confirmed by previous in vitro assays [ 12 ]. Importantly, our live-cell observations revealed that Li 1 cells showed defective dynamic behavior of the actin cytoskeleton, compared with that of the wild-type control ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Actin is one of the most conserved proteins in eukaryotes. Structural predictions suggested that the G65V substitution would affect the polymerization capability of GhACT17DM, as confirmed by previous in vitro assays [ 12 ]. Importantly, our live-cell observations revealed that Li 1 cells showed defective dynamic behavior of the actin cytoskeleton, compared with that of the wild-type control ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 75%
“…Thyssen et al also identified Gh_D04G0865 as the Li 1 candidate, labeled by a SNP marker, CFB11927 (23,783,515 bp in G. hirsutum Chr D04), using sequencing-mapping and VIGS [ 11 ]. The experiment carried out by Thyssen et al used a 354-bp fragment from the conservative domain of actin C-terminal sharing high similarity among actin members that would not discriminate the actin families in VIGS, which resulted in a Li 1 -like phenotype but in a different mechanism [ 12 ]. Benefiting from the whole genome sequencing of upland cotton [ 25 ], we now know that 37 actin genes with complete NBDs sharing high identity occur in the TM-1 genome, including Gh_D04G0865 ( Figure S3 , labeled by black square).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations